Landscape and regulation of mRNA translation in the early C. elegans embryo - Yash Shukla; Vighnesh Ghatpande; Cindy F. Hu; Daniel J. Dickinson; Can Cenik (Cell Reports)
Summary: Animal embryos rely on regulated translation of maternally deposited mRNAs to drive early development. Using low-input ribosome profiling combined with RNA sequencing on precisely staged embryos, we measure mRNA translation during the first four cell cycles of C. elegans development. We uncover stage-specific patterns of developmentally coordinated translational regulation. Our results confirm that mRNA localization correlates with translational efficiency, though initial translational repression in germline precursors occurs before P-granule association. Our analysis suggests that the RNA-binding protein OMA-1 represses the translation of its target mRNAs in a stage-specific manner while indirectly promoting the translational efficiency of other transcripts. These findings illuminate how post-transcriptional mechanisms shape the embryonic proteome to direct cell differentiation, with implications for understanding similar regulation across species where maternal factors guide early development.